Design of Sustainable Building by Considering Green Materials – Case Study in Salalah Oman - Al Kathiri, Ahmed; Damdelen, Omer (Technium: Romanian Journal of Applied Sciences and Technology, 2022)
The present study is based on analyzing the sustainable approaches toward adaptation of green building , materials and technology. The implemented standards to reduce resource and energy usage is applied to improve the living standards of people and society. The study is focused on construction industry of Oman and consider fiver case studies from Salalah based on designing green building in Dhofar region. The green building and construction is rated according to standards provided by LEED organization. The study compare the case studies and develop model for sustainable building. The simulation results indicates the improtance of green building in saving energy and resources such as Eco-house.